Nutrient intake, digestibility, performance, carcass traits and sensory analysis of meat from lambs fed with co-products of Amazon oilseeds - de Castro, Vinicius Costa Gomes; Budel, Juliana Cristina de Castro; Rodrigues, Thomaz Cyro Guimarães de Carvalho; Silva, Bruna Almeida; de Lima, Alyne Cristina Sodré; de Souza, Shirley Motta; da Silva, Jamile Andréa Rodrigues; Joele, Maria Regina Sarkis Peixoto; Silva, André Guimarães Maciel e; Lourenço-Junior, José de Brito (Frontiers in Veterinary Science, 2023)
The increase in availability and nutritional composition of oilseed by-products has made it essential to study the use of this biomass. The objective of this work was to investigate the effects of including oilseed cakes on intake and digestibility, performance, carcass characteristics and meat sensory in feedlot lambs. Twenty-four crossbred Dorper x Santa Inês lambs, with initial body weight of 30 ± 1.3 kg, male, castrated, aged 4 to 5 months, were distributed in a completely randomized experimental design with four treatments (diets) and six replications (animals), confined in individual stalls for 70 days. The inclusion of Tucuma cake (Tuc) reduced dry matter intake (P < 0.01) and diets with Cupuassu cake (Cup) and Palm kernel (Palm) reduced dry matter digestibility (P < 0.05). The Tuc diet also provided the lowest final body weight (P = 0.02); lower average daily gain (P = 0.03); lower feed efficiency (P = 0.03) and lower carcass weight (P < 0.01). However, diets did not influence carcass yield (%), fat thickness (mm) and loin eye area (cm²) (P > 0.05). Meat from lambs on the control diet was rated as less fibrous and more tender (P < 0.05). The inclusion of tucuma cake does not influence digestibility, but reduces intake, performance and influences carcass characteristics and meat texture. Diets with cake of cupuassu and palmiste reduced digestibility, however, intake, performance and carcass characteristics were similar to the control diet.